2011
DOI: 10.1007/s10329-011-0274-2
|View full text |Cite
|
Sign up to set email alerts
|

Patch depletion behavior differs between sympatric folivorous primates

Abstract: Food competition in group-living animals is commonly accepted as a critical determinant of foraging strategies and social organization. Here we examine food patch depletion behavior in a leaf-eating (folivorous) primate, the guereza (Colobus guereza). Snaith and Chapman (2005) studied the sympatric folivorous red colobus (Procolobus rufomitratus), which shares many food resources with the guereza. They determined that red colobus deplete the patches (feeding trees) they use, while we found contrary evidence fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 36 publications
1
24
1
Order By: Relevance
“…However our data also revealed that assumptions regarding the nutrient content of individual foods consumed by primates are sometimes incorrect. For example, although it is often assumed that immature and mature leaves ingested by primates differ in fiber, available protein, and secondary metabolites [Chapman & Chapman, 2002;Milton, 1979;Mowry et al, 1996;Tombak et al, 2012], mature and young leaves consumed by howler monkeys in the present study did not differ in their nutritional components. Given …”
Section: Phytochemical Composition Of the Dietcontrasting
confidence: 49%
“…However our data also revealed that assumptions regarding the nutrient content of individual foods consumed by primates are sometimes incorrect. For example, although it is often assumed that immature and mature leaves ingested by primates differ in fiber, available protein, and secondary metabolites [Chapman & Chapman, 2002;Milton, 1979;Mowry et al, 1996;Tombak et al, 2012], mature and young leaves consumed by howler monkeys in the present study did not differ in their nutritional components. Given …”
Section: Phytochemical Composition Of the Dietcontrasting
confidence: 49%
“…Thus, the abundance and species diversity of seeds within latrines is expected to be lower in fragments where spider monkeys usually spend more time consuming leaves [18], [30], and the number of feces without seeds is usually higher than in continuous forests [19]. However, we also predict that fruit scarcity in fragments will ‘force’ spider monkeys to spend more time consuming the available fruit patches; i.e., they will deplete the available patches more intensively than in continuous forest sites [34], [35]. As consequence, the seed rain in fragments will be dominated by a few plant species, reducing the number of common ( 1 D) and dominant species ( 2 D), as well as the seed community evenness in forest fragments.…”
Section: Introductionmentioning
confidence: 86%
“…To determine if leaves can be a superabundant fallback food, we need to know if the leaf quality that is required for the animal's digestive ability to extract sufficient nutrients is suitable, and that leaf production of this required quality is sufficiently high to maintain the primate population. This information is generally unavailable, but there is a growing body of evidence that even folivorous primates experience food competition (Snaith and Chapman 2007;Tombak et al 2012).…”
Section: Coping With Seasonality: Two Hypotheses On Resource Limitationmentioning
confidence: 99%